In vitro study of color stability of polycrystalline and monocrystalline ceramic brackets - Cibele Braga de Oliveira; Luiz Guilherme Martins Maia; Ary Santos-Pinto; Luiz Gonzaga Gandini Júnior (Dental Press Editora, 2014)
OBJECTIVE: The aim of this in vitro study was to analyze color stability of monocrystalline and polycrystalline ceramic brackets after immersion in dye solutions. METHODS: Seven ceramic brackets of four commercial brands were tested: Two monocrystalline and two polycrystalline. The brackets were immersed in four dye solutions (coffee, red wine, Coke and black tea) and in artificial saliva for the following times: 24 hours, 7, 14 and 21 days, respectively. Color changes were measured by a spectrophotometer. Data were assessed by Multivariate Profile Analysis, Analysis of Variance (ANOVA) and Multiple Comparison Tests of means. RESULTS: There was a perceptible change of color in all ceramic brackets immersed in coffee (ΔE* Allure = 7.61, Inspire Ice = 6.09, Radiance = 6.69, Transcend = 7.44), black tea (ΔE* Allure = 6.24, Inspire Ice = 5.21, Radiance = 6.51, Transcend = 6.14) and red wine (ΔE* Allure = 6.49, Inspire Ice = 4.76, Radiance = 5.19, Transcend = 5.64), but no change was noticed in Coke and artificial saliva (ΔE < 3.7). CONCLUSION: Ceramic brackets undergo color change when exposed to solutions of coffee, black tea and red wine. However, the same crystalline structure, either monocrystalline or polycrystalline, do not follow the same or a similar pattern in color change, varying according to the bracket fabrication, which shows a lack of standardization in the manufacturing process. Coffee dye produced the most marked color changes after 21 days of immersion for most ceramic brackets evaluated.